Farmer Saved Peanut Seed: Factors to Consider - Barry L. Tillman; Daniel W. Gorbet; Elmo B. Whitty (EDIS)
Revised! Originally published in 2002 as "Peanut Variety Protection", SS-AGR-186, a 5-page fact sheet by B.L. Tillman, D.W. Gorbet, and E. B. Whitty, outlines and discusses the benefits and risks associated with purchasing peanut seed as compared to saving it from the farm. In this revision, authors Tillman and Gorbet revise and expand upon Whitty's original publication to address economic and seed quality considerations. Also added is a table listing the legal protection status of certified seed varieties available in 2005. Published by the UF Department of Agronomy, July 2006.